2003
DOI: 10.1093/jnci/95.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Effects in Oncology

Abstract: In randomized double-blinded, placebo-controlled trials, presumably with minimum sources of bias, placebos are sometimes associated with improved control of symptoms such as pain and appetite but rarely with positive tumor response. Substantial improvements in symptoms and quality of life are unlikely to be due to placebo effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 74 publications
(146 reference statements)
2
68
0
1
Order By: Relevance
“…The so-called 'additive model' assumed that drug and placebo effects are additive in the drug arm of the study, thus subtracting the response in the placebo arm from the response in the drug arm would allow to researchers to assess the true efficacy of a drug (13). The placebo effect has been defined as 'the effect seen in a patient who has received an intervention which is believed to lack a specific action' (14,15). Since the first modern description by Beecher in 1955 (16), it has been reported that over 35% of patients are improved or cured by the placebo effect, although it has been suggested that this rate of response is overestimated (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The so-called 'additive model' assumed that drug and placebo effects are additive in the drug arm of the study, thus subtracting the response in the placebo arm from the response in the drug arm would allow to researchers to assess the true efficacy of a drug (13). The placebo effect has been defined as 'the effect seen in a patient who has received an intervention which is believed to lack a specific action' (14,15). Since the first modern description by Beecher in 1955 (16), it has been reported that over 35% of patients are improved or cured by the placebo effect, although it has been suggested that this rate of response is overestimated (14).…”
Section: Discussionmentioning
confidence: 99%
“…The placebo effect has been defined as 'the effect seen in a patient who has received an intervention which is believed to lack a specific action' (14,15). Since the first modern description by Beecher in 1955 (16), it has been reported that over 35% of patients are improved or cured by the placebo effect, although it has been suggested that this rate of response is overestimated (14). Greater effects are observed for subjective sensations, psychological disorders or for relief of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These diseases are bacterial infection, infertility, viremia, pneumothorax, and uremia. Placebo effects are known to be minimal in cancer, so we also considered hepatocellular carcinoma and renal cell carcinoma as negative examples given that previous reports show that very low placebo responses were observed in trials of these 2 malignancies (20).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic diseases, vascular diseases, and heart diseases are also proximate to the placebome module, which is consistent with the results of the WGHS analysis above. Some of the diseases proximate to the placebome, such as neoplasm-related diseases, bone fractures, or RNA virus infections, are not clinically known to have objective placebo responses that change pathophysiology (20); the proximity of these diseases suggests that there may be a subset of diseases in which the placebo response can be activated, but lacks efficacy. Thus, activation of a placebo response may not always lead to amelioration of a specific clinical condition.…”
Section: Resultsmentioning
confidence: 99%